A lanthanum-barium-borovanadate glass containing Bi2O3 for radiation shielding applications. (September 2021) - Kurtulus, Recep; Sayyed, M.I.; Kavas, Taner; Mahmoud, K.A.; Tashlykov, O.L.; Khandaker, Mayeen Uddin; Bradley, D.A.
Abstract: Radiation shielding materials are of prime importance for weighing the benefit-to-risk of ionizing radiation. In this perspective, a lanthanum-barium-borovanadate (BVBL) glass containing varying amounts of bismuth oxide (Bi2 O3 ) is studied in this work. The glass composition of 5La2 O3 –10BaO-(65-x)B2 O3 –20V2 O5 -xBi2 O3 where x: 0, 3, 6, 9, 12, 15 mol% has been purposed, and thus six different glass series with BVBL0 to BVBL15 coded were investigated for the physical, mechanical, and radiation shielding features. Physical property calculations revealed that the glass density increase from 3.1685 to 4.1345 g cm -3 with the insertion of Bi2 O3 from 0 to 15 mol%. Furthermore, mechanical properties in terms of the Mackenzie-Makishima model demonstrated that Young's, bulk, shear, and longitudinal moduli were reduced following the concentration of Bi2 O3 . In particular, the BVBL0 sample showed the best mechanical moduli amongst others. Radiation shielding competencies were ascertained by using Phy-X/PSD and Monte Carlo N-Particle Transport Code (MCNP-5). The theoretical computations via Phy-X/PSD clearly indicated that the linear attenuation coefficient (LAC) showed enhanced characteristics with the increasing content of Bi2 O3 . Based upon the determined LAC, the other essential parameters such as half-value layer (HVL), effective atomic number (Zeff ), and transmission factor (TF) were also assessed. Moreover, the MCNP-5 simulation demonstrated that the BVBL15 sample provided the best radiation attenuation compared to the undoped BVBL0. Moreover, both Phy-X/PSD and MCNP5 studies displayed good agreement with each other. Overall, we concluded that Bi2 O3 seems to be a strong candidate for improving radiation attenuation coefficients in the BVBL glass system. Highlights: The ascending doping rate in Bi2 O3 leads to the increment of the overall ρ glass from 3.1685 to 4.1345 g/cm 3 . The highest LAC values are relevant to the BVBL15. MCNP-5 and Phy-X/PSD computations revealed a good agreement with each other. Mechanical moduli decreased as the Bi2 O3 content increased.